Polish and Finnish students views on andropause.Part I. Opinions on andropause and knowledge about its symptoms - Pryczek, Katarzyna; Bielawska-Batorowicz, Eleonora (Menopause Review/Przegląd Menopauzalny, 2007)
Objective: The aim of the study was to describe opinions on andropause among Polish and Finnish students and to evaluate how gender and nationality affect the level of knowledge and its correctness. The study was designed as cross-sectional. All measures were taken at the same time. Material and methods: 224 students from Łodź and Tampere participated in the study. The Polish sample included 62 females and 54 males, and the Finnish sample included 62 females and 46 males. Two questionnaires were administered: Opinions on andropause and Andropausal symptoms . Both were designed for this study in Polish and Finnish language versions. Results: Opinions on andropause and knowledge of its symptoms included both false and correct elements. Statistical analysis of scores from the Opinions on andropause questionnaire revealed neither a main effect of gender or nationality nor an interaction effect. However, differences were found when particular opinions were compared, e.g. in relation to treatment or sexual activity. Knowledge of andropausal symptoms is significantly higher among female subjects and among Polish participants. No interaction effect was found, however. Conclusions: Gender and nationality do not affect opinions on andropause, but have an effect on knowledge about andropausal symptoms. Women usually reveal wider and more correct knowledge of andropause. As the information on andropause is incomplete and often false, it is worth considering the promotion of information that might result in reduction of stereotypes and implementation of health-related behaviours.